Remembering Fraud in the Future: Investigating and Improving Auditors' Attention to Fraud during Audit Testing* - Austin, Ashley A. (Contemporary Accounting Research, 2023)
ABSTRACT During the testing stages of the audit, auditors must divide their attention simultaneously between (i) performing the planned audit procedures and (ii) remaining broadly skeptical and alert for fraud. Regulators note instances in which auditors do not take actions that effectively respond to fraud risks during these later stages, suggesting auditors may devote insufficient attention to fraud while they are busy executing the planned audit procedures. Leveraging prospective memory theory, I identify and test an intervention that can improve auditors' attention to fraud by encouraging auditors to have implementation intentions—that is, more detailed plans about when and how they will consider fraud. I find that encouraging implementation intentions interacts with auditors' perceived fraud task importance to increase auditors' attention to fraud when this attention would otherwise be lower, making auditors more likely to take effective fraud actions. Importantly, these results also indicate that, even in a high fraud risk setting, auditors may devote insufficient attention to fraud while performing the planned audit procedures, confirming concerns voiced by regulators. However, my study also highlights concerns about regulators' inspection processes prompting auditors to focus too heavily on inspection risk, as the results suggest auditors are less likely to detect fraud in high‐risk audit areas thought to have low inspection risk.